Sobre a inclusão de alunos com autismo na escola regular. Quando o campo é quem escolhe a teoria - SERRA, Dayse (2010)
This article deals with the problem of the inclusion of the autistic students in the regular educational system. Over time, the educational inclusion has been transforming itself into the right of the students who are bearers of deficiency, but it is possible to observe that their inclusion is not yet confirmed in a proper way in the everyday life of the school. Although it is possible to find the matter of inclusion in many legal documents, the lack of public policies becomes difficult the organization of the pedagogic practices which allow the permanence of the autistic students in the regular school.